THE PHILOSOPHICAL FOUNDATIONS OF VIRTUOUS SOCIETY: ANALYZING ABU NASR FARABI’S VISION IN “THE CITY OF VIRTUOUS PEOPLE” - Nutfullo Nasrulloevich Teshaev (Journal of Learning on History and Social Sciences, 2024)
In the Eastern world, particularly in Uzbekistan, the concept of communal living is not merely a practical arrangement but a profound ethos that binds individuals’ together, nurturing mutual solidarity and establishing a fundamental societal structure. This communal lifestyle holds significant sway over the formation and evolution of individual beliefs, cultural values, and collective identity. When exploring the elevated expressions of spirituality observed in our region, such as the widespread virtues of kindness and generosity, it becomes imperative to delve into their socio-philosophical origins. These virtues are not incidental traits but are deeply rooted in the historical, philosophical, and cultural fabric of Eastern societies, including our own. They serve as moral compass points that guide interpersonal relations, community dynamics, and broader societal development, reflecting a heritage of shared wisdom and communal resilience that continues to shape our nation’s cultural landscape.